The Association between Daily Contact, Working Period and Biosecurity to Colonization of Extended-Spectrum Beta Lactamase-Producing Escherichia coli of Poultry Workers - Eustachius Hagni Wardoyo; Sonya Ananda Elya John; Muhamad Ali (Jurnal Penelitian Pendidikan IPA, 2024)
Extended-spectrum beta lactamase producing Escherichia coli (ESBL-Ec) colonization in poultry worker is one prominent of zoonotic problem, in which of it, daily contact, working period and biosecurity play role. This study aimed to identify association between daily contact, working period and biosecurity to ESBL-Ec’ colonization. Rectal swab was applied to poultry workers to identify phenotypic ESBL-Ec. Duration of contact, working period and biosecurity parameter data was obtained through structured questionnaire. A number of 51 poultry workers with a mean age of 42.7 years, and 54.9% are male. Nineteen poultry workers (37.3%) was tested positive for ESBL-Ec. Daily contact of ≥ 2 hours is not significant (p = 0.291; 95% CI) while working period of ≥ 3 years is significant (p = 0.024; 95% CI) to ESBL-Ec’ colonization. Twenty-one biosecurity parameters were measured, with 3 parameters significant association: sick chicken isolation (p = 0.022), existence of quarantine shed (p = 0.018) and past biosecurity training (p = 0.047). In conclusion, working period ≥ 3 years, sick chicken isolation, existence of quarantine shed and past biosecurity training is associated with ESBL-Ec’ colonization to farmer.